Microplastic Contamination on the Beaches of South China - Chai, Bingwen; Li, Yanping; Wang, Li; Zhang, Xiao-Tan; Wan, Yi-Ping; Chen, Fengyuan; Ma, Jie; Lan, Wenlu; Pan, Ke (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. Sandy beach is a fragile environment that deserves our special attention in the aspect of MP contamination, as this area is a hotspot accumulating large quantity of plastic waste. But our understanding of MP distribution and the scale of contamination on beaches is far from enough. This study investigated the occurrence and characteristics of MPs on fourteen beaches along the coasts of South China. MPs were ubiquitously distributed in the sand and most of the beach MPs had a small size less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting a diverse types of MPs are present on the beaches. Polyethylene (PE) and polypropylene (PP) were more abundant than other types of MPs here. The abundance of MPs was higher in the upper layers of the beach than the deeper layers in one of the sampling sites. Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More efforts are needed to clarify the vertical distribution of MPs on beach, especially for those MPs less than 1 μm.